Mutation in CATIP (C2orf62) causes oligoteratoasthenozoospermia by affecting actin dynamics. Issue 2 (5th June 2020) - Arafat, Maram; Harlev, Avi; Har-Vardi, Iris; Levitas, Eliahu; Priel, Tsvia; Gershoni, Moran; Searby, Charles; Sheffield, Val C; Lunenfeld, Eitan; Parvari, Ruti
Abstract : Background: Oligoteratoasthenozoospermia (OTA) combines deteriorated quantity, morphology and motility of the sperm, resulting in male factor infertility. Methods: We used whole genome genotyping and exome sequencing to identify the mutation causing OTA in four men in a consanguineous Bedouin family. We expressed the normal and mutated proteins tagged with c-Myc at the carboxy termini by transfection with pCDNA3.1 plasmid constructs to evaluate the effects on protein stability in HEK293 cells and on the kinetics of actin repolymerisation in retinal pigment epithelium cells. Patients' sperm samples were visualised by transmission electron microscopy to determine axoneme structures and were stained with fluorescent phalloidin to visualise the fibrillar (F)-actin. Results: A homozygous missense mutation in Ciliogenesis Associated TTC17 Interacting Protein ( CATIP ): c. T103A, p. Phe35Ile, a gene encoding a protein important in actin organisation and ciliogenesis, was identified as the causative mutation with a LOD score of 3.25. The mutation reduces the protein stability compared with the normal protein. Furthermore, overexpression of the normal protein, but not the mutated protein, inhibits repolymerisation of actin after disruption with cytochalasin D. A high percentage of spermatozoa axonemes from patients have abnormalities, as well as disturbances in the distribution of F-actin. Conclusion: This is the first report of a recessive mutation in CATIP in humans. The identified mutation may contribute to asthenozoospermia by its involvement in actin polymerisation and on the actin cytoskeleton. A mouse knockout homozygote for CATIP was reported to demonstrate male infertility as the sole phenotype.